Prevalence of low back pain and disc degeneration in elite cross-country skiers: A comparative study with non-athlete controls - Aavikko, A.; Pesonen, J.; Ristolainen, L.; Murto, N.; Kautiainen, H.; Lund, T. (Scandinavian Journal of Medicine & Science in Sports, 2025)
Intensive training in competitive sports during childhood and adolescence may increase the risk of low back pain (LBP). While disc degeneration (DD) is a known contributor to LBP, its occurrence among elite cross-country skiers has not been previously assessed using magnetic resonance imaging (MRI). This study aimed to compare the prevalence of LBP and DD in elite cross-country skiers and age-matched non-athlete controls. Forty-four elite skiers and 71 controls underwent a structured interview assessing LBP without specific trauma, a clinical examination, and lumbar spine MRI. Skiers also completed patient-reported outcome measures (PROMs). Disc morphology was evaluated from MRI using the Pfirrmann classification (grades 1-5). A Pfirrmann Summary Score (PSS) was calculated by summing the grades of the individual discs. Analyses were adjusted for age and sex. LBP was reported by 75% of skiers and 54% of controls (p = 0.028). DD prevalence, defined as at least one disc graded >= 3, did not differ significantly between the groups (50% versus 42%, p = 0.78). In both groups, individuals with LBP had significantly higher PSS than their asymptomatic peers. Elite skiers reported more LBP than controls, despite similar DD prevalence. These findings suggest that while intensive training may not increase DD risk, it may contribute to a higher burden of LBP. The association between PSS and LBP was consistent across groups, indicating that structural disc changes may play a role regardless of athletic status.